Cytochrome b diversity of Hungarian Botrytis cinerea strains - Asadollahi, Mojtaba; Fekete, Éva; Fekete, Erzsébet; Karaffa, Levente; Irinyi, László; Sándor, Ersébet (Acta Agraria Debreceniensis, 2010)
In the mitochondrion of eukaryotes, cytochrome b is a component of respiratory chain complex III. Cytochrome b is encoded by the cytochrome b (CYTB) gene located in the mitochondrial genome. The fungicidal activity of QoIs relies on their ability to inhibit mitochondrial respiration by binding at the so-called Qo site (the outer quinol-oxidation site) of the complex III. Since their introduction, QoIs (like azoxystrobin) have become essential components of plant disease control programs because of their wide-ranging efficacy against many agriculturally important fungal diseases like grey mould on various crops. QoI resistance primarily arises from a target-site-based mechanism involving mutations in the mitochondrial CYTB. As the management of grey mould is often dependent on chemicals, the rational design of control programs requires the information about the diversity of genes connected with resistance in field populations of the pathogen. Monospore B. cinerea field isolates has been collected during 2008-2009 from different hosts in Hungary. PCR fragment length analysis indicated the high frequency presence of type large intron in the isolates while in a few strains G143A substitution could also be detected. These results indicated the heterogeneity of CYTB in the Hungarian B. cinerea populations, which possibly involve the heteroplasmy of this mitochondrial gene, moreover indicates the existence op azoxystrobin resistant populations in Hungary. This work was supported by NKFP-A2-2006/0017 grant. Erzsébet Fekete is a grantee of the János Bolyai Scholarship (BO/00519/09/8).